2006
DOI: 10.3892/or.15.5.1185
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and tumor 5-FU sensitivity in patients with stage IV colorectal cancer and peritoneal dissemination

Abstract: Abstract. Among 125 patients with peritoneal dissemination (P1-3) of colorectal cancer, including those with other synchronous metastases, the 5-year overall survival (OS) rate was 13.3% for P1 patients (n=30), 12.8% for P2 patients (n=39), and 1.8% for P3 patients (n=56) (P1 vs. P2, p=N.S.; P2 vs. P3, p=0.02; P1 vs. P3, p=0.001), while the median survival time (MST) was 12.0, 14.1, and 3.1 months, respectively. The 5-year OS rates for patients who had peritoneal dissemination without other metastases were 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Fivefluorouracil (5-FU), a fluorinated pyrimidine analog, has been widely used in adjuvant chemotherapy for advanced CRC. However, the prognosis of CRC patients and the correlation between epigenetic changes in 5-FU adjuvant chemotherapy remain controversial (de Vos tot Nederveen Cappel et al, 2004;Crozier et al, 2006;Hasegawa et al, 2006). On the other hand, a relatively higher frequency of APC (germline or somatic) mutations in sporadic CRC has been reported in other ethnic groups (Esteller et al, 2000;Fearnhead et al, 2001;Kámory et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fivefluorouracil (5-FU), a fluorinated pyrimidine analog, has been widely used in adjuvant chemotherapy for advanced CRC. However, the prognosis of CRC patients and the correlation between epigenetic changes in 5-FU adjuvant chemotherapy remain controversial (de Vos tot Nederveen Cappel et al, 2004;Crozier et al, 2006;Hasegawa et al, 2006). On the other hand, a relatively higher frequency of APC (germline or somatic) mutations in sporadic CRC has been reported in other ethnic groups (Esteller et al, 2000;Fearnhead et al, 2001;Kámory et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the incidence of postoperative peritoneal dissemination is about 10% for colorectal cancer, which is much lower than for gastric cancer (33). Although long-term survival of stage IV colorectal cancer patients without peritoneal dissemination has been reported, the prognosis is very poor after occurrence of peritoneal dissemination (33). Colorectal cancer differs from gastric cancer with respect to the mode of recurrence/metastasis and its biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Stage II/III gastric cancer positive for LN metastasis is associated with peritoneal dissemination in at least 30-40% of patients who undergo surgery. There are two known mechanism of peritoneal dissemination, which are tumor cell dissemination to the peritoneal lining via lymphatics and direct spread of free cancer cells from sites of serosal exposure followed by survival/proliferation in the peritoneal cavity (33). It is also possible that gastric cancer may metastasize to intramural LNs, enter the greater omentum via lymphatics, and then be directly implanted into the abdominal wall and peritoneum (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the 5-year survival of these patients after systemic chemotherapy is still poor and ranges from 0-22%. [1,3,4,8,14,17,20,21,25,27,28,30,36] In the last two decades, the combination of cytoreductive surgery (CRS) and perioperative intraperitoneal chemotherapy (PIC) have been developed rapidly and considered as an innovative technique for CRPC. PIC consists of hyperthermic intraperitoneal chemotherapy (HIPEC) and early postoperative intraperitoneal chemotherapy (EPIC).…”
Section: Introductionmentioning
confidence: 99%